P11.03.B BXQ-350: Modulating ceramide and Sphingosine-1-Phosphate for anti-tumor activity and potential mitigation of chemotherapy induced peripheral neuropathy. (5th September 2022) - Tapolsky, G H; Morris, J C; Yilmaz, E; Villano, J L; Muller, C; Curry, III, R C; Puduvally, V K; Wise-Draper, T M; Takigiku, R; Wesolowski, R
Abstract: Background: Sphingolipids are a class of bioactive signaling molecules implicated in multiple cellular processes and molecular pathways. Many publications have indicated that among these sphingolipids, sphingosine-1-phosphate (S1P) is a key sphingolipid that promotes cancer cell survival and proliferation, activates multiple oncogenic pathways, and stimulates immuno-suppressor cell populations promoting a pro-tumoral microenvironment. Many of these publications have also implicated S1P with chemotherapy induced peripheral neuropathy, a debilitating and serious side effect that may impact therapeutic treatments and patient's quality of life. Material and Methods: BXQ-350 is a nanovesicle of Saposin C, an allosteric activator of sphingolipid metabolism, that has broad anticancer activity, potentially in part by lowering systemic S1P levels. BXQ-350 was investigated in a Phase 1 dose-escalation safety study in an all-comer cancer patients with advanced solid malignancies, including CNS tumors (NCT02859857) to determine its safety profile and its potential clinical activity as a single agent in cancer patients. Samples were collected to determine pharmacokinetics and explore potential biomarkers. Results: 11 patients (~15% of evaluable patients) with advanced disease had a clinical benefit and amongst these, 8 patients (~11% of evaluable patients) had PFS> 6 months with 2 patients still on study five years after enrollment. Analysis of patient's samples revealed that BXQ-350 decreases systemic S1P levels in the majority of the patients experiencing a clinical benefit. In addition, several patients with established CIPN spontaneously reported improvements of their symptoms shortly after BXQ-350 administration. Analysis of these patients' samples also revealed that S1P systemic levels had decreased, as well as pro-inflammatory cytokines associated with CIPN. Conclusion: While these results are exploratory and preliminary in nature, they suggest that BXQ-350's mechanism of action may represent a novel anti-cancer approach that may also mitigate CIPN.